The mangrove coast eaudiobook - Wayne White, Randy (Doc Ford, 2003)
One of the best Florida crime writers around, Randy Wayne White is also a journalist, expert fishing guide, and the bestselling author of Shark River. In The Mangrove Coast, he pens a suspenseful, skillfully plotted tale featuring the inimitable marine biologist, Doc Ford. Doc Ford is hot on the trail of his recently deceased war buddy's missing wife. Rumor has it that she vanished into the steamy jungles of South America in the company of an unsavory specimen of humanity. From Florida to Colombia and Panama, he traces their path. But a shadowy figure is closing in on Doc—and the violence left in wake of this enigmatic individual is absolutely terrifying. Of White, author Carl Hiaasen has said "(he) ... takes us places that no other Florida mystery writer can hope to find." The Mangrove Coast blends distinctive atmosphere with action for a tropical thrill ride listeners won't soon forget. "We'll drop anything we're doing to read a new Randy Wayne White book and be glad we did."—Denver Post